Arbitration and Mediation: An Economic Perspective - Paola Manzini; Marco Mariotti (Institute for the Study of Labor (IZA), 2002)
This paper deals with the effects that intermediation has on strategic behaviour in negotiations. To this end, we use the tools of game theory to analyse how different institutional settings can provide specific strategic incentives and thereby condition the outcome of negotiations. We concentrate on some very recent contributions which have addressed gaps in this literature and stress the economic institution behind some predicted behaviours.
Keywords: J52; 330; arbitration; mediation; bargaining; Verhandlungstheorie; Schiedsgerichtsbarkeit; Mediation; Theorie